Control Rodents at Poultry Farms to Mitigate the Risk of Salmonella. A Comprehensive Review - Mubarik Ali; Norina Jabeen; Qamar Ullah; Hafiz Abdul Majid; Abdul Wadood Jan; Hamza Maris; Muhammad Atif (Indus Journal of Bioscience Research, 2024)
A major but sometimes underestimated problem in chicken farms are rodent infestations, which seriously compromise public safety, health and economy. The function of rats as Salmonella carriers is investigated in this thorough overview together with their effects on public health, poultry health and farm output. Particularly rats and mice, rodents may readily access feed, water and nesting sites inside poultry farms, therefore contaminating the food and spreading diseases as well as causing damage to the infrastructure. Main disease connected to rodent activities, salmonella can contaminate the surroundings and infect poultry by means of rodent urine, saliva and feces. This impairs poultry health and product safety in turn, therefore allowing Salmonella-contaminated eggs and meat to find their way into the human food chain. Emphasizing an integrated pest management method including cleanliness, physical barriers, traps, baits and biological control techniques, the review investigated the successful rodent control strategies. Part of the complete control plan is also the possible employment of contemporary surveillance technologies such motion-activated cameras and remote monitoring systems based on LoRaWAN. These techniques help chicken growers lower disease transmission, control rodent numbers and protect public health in addition to poultry.